Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae) - Kosterin, Oleg E.; Kompier, Tom (Zootaxa, 2017)
Coeliccia rolandorum sp. nov. is described from the eastern Cambodia (holotype: Cambodia, Mondulkiri Province, Buu Sraa Waterfall environs, 12°34' N 107°24' E, ~780 m a.s.l., 16 June 2014, RMNH) and southern and central Vietnam. It is related to C. kazukoae, which is known from the Cardamom and Sankamphaeng Mts., and replaces it in eastern Indochina. New distributional data on C. kazukoae are presented and its characters are discussed with respect to their change with age.